Sowing depth and light intensity on the emergence and development of weeds - Sasso Ferreira Souza, Guilherme (Revista Ciência Agronômica, 2021)
Weeds are one of the ecological factors that directly affect agricultural costs. Thus, understanding the emergence anddevelopment of these species is essential for the decision-making on weed control strategies. This study aims to evaluate the effect ofdifferent sowing depths and luminous intensities under fi eld conditions on the emergence and development of the Acanthospermumaustrale (Loefl .) Kuntze and Ipomoea grandifolia (Dammer) O’Donell. Each species constituted one experiment, and the completelyrandomized design with four repetitions was adopted. The treatments were arranged in a 6 x 4 factorial scheme, with six sowing depths(0.5; 1.0; 2.0; 4.0; 8.0; and 12.0 cm) associated with four luminous intensities (100%, 70%, 50%, and 30% sunlight) obtained usingshade cloths. The emergence of seedlings was evaluated daily to obtain the emergence and the emergence speed index. Plantheight(length), the period until flower induction, and the dry matter of plants during flowering were also analyzed. A. australeand I. grandifolia emerge under the luminous intensities of 100, 70, 50, and 30% of solar radiation and in sowings depths upto 12.0 cm. Nevertheless, A. australe is the only one affected by luminous intensity, sowing depth, and the interaction betweenboth factors in all the analyzes conducted. Luminous intensity reduction leads to lower development of I. grandifolia.